Relevance of oncobiome in breast cancer evolution in an Argentine cohort - Dandeu, Leonardo Néstor Rubén (2025)
Breast cancer is the leading cause of cancer deaths in women worldwide, with about 20,000 cases annually in Argentina. While age, diet, and genetics are known risk factors, most breast cancer cases have unknown causes, necessitating the discovery of new risk factors. The aim of this study was the analysis of the prognostic relevance of the oncobiome in Argentinean breast cancer patients. Sequencing of the V4 region 16S rRNA gene was performed on 34 primary breast tumor samples, using bioinformatic and statistical analyses to identify bacteria and hypothetical pathways. Each sample presented a unique microbial profile, with Proteobacteria being the most abundant phylum. Tumors >2 cm showed greater alpha diversity with increased nucleotide biosynthesis. Moreover, progesterone-receptor tumors showed differences in beta diversity, being progesterone receptor-positive tumors that had the highest expression of Acinetobacter and Moraxella. In disease progression, the phylum Chloroflexi was prevalent in tumors of surviving patients. Acinetobacter and Cloacibacterium genera were significantly higher in patients without events and those without metastasis. We found that nucleotide and cell-structure biosynthesis, and lipid metabolism pathways were enriched in tumors with poor progression, whereas amino-acid degradation was increased in tumors of surviving patients. This finding is an indication that tumor cells are taking advantage of this effect of the microbiome during tumor progression. We conclude that oncobiome is dysbiotic in these patients, with distinct patterns in those with poor progression. Suggesting a link between the oncobiome and cancer progression, paving the way for new therapies to improve patient quality of life and survival.